Empowering Pregnant Women Through Psychoeducation with A Combination of Mindfulness to Improve Mental Health - Ulfa, Maria; Tina Sari, Levi; Wibisono, Wahyu (STIKes Patria Husada Blitar, 2024)
The maternal mortality rate in East Java in 2022 was 499 maternal deaths. Blitar Regency reached 17 deaths and Blitar City only had 3 maternal deaths. Tulungrejo Village, Wates District, Blitar is the place of this community service. The geographical location of Tulungrejo Village is in the mountains of southern Blitar. In 2023, 25 women were married at the age of under 19 years and had their first child at the age of 18, 20 people. Early marriage can cause mental health problems, due to psychological unpreparedness for marriage, facing pregnancy at a young age, and unpreparedness of reproductive organs, which can increase the risk of developing eclampsia or eclampsia. The interventions to reduce maternal mortality were by improving maternal mental health through psychoeducation combined with mindfulness. There were stages in implementing community service activities: the first stage was to socialize the community service program with the Head of Tulungrejo Village, the Secretary, the Head of the Welfare Section, and midwives in the Tulungrejo Village area. The second stage was psychoeducation training with a combination of mindfulness. The third stage was the application of technology with the